Analisis Kemampuan Berpikir Kreatif Matematis Siswa SMP Berdasarkan Kerangka ACER - Dhita Fachriyanti; Ary Woro Kurniasih (FKIP Universitas Mataram, 2026)
This study aims to describe the mathematical creative thinking abilities of eighth-grade junior high school students in the area of plane figures at a school in Grobogan Regency using the ACER (Australasian Council for Educational Research) framework. A descriptive qualitative approach was applied in this study. A total of 34 eighth-grade students were selected as the sample and grouped based on their level of mathematical creative thinking ability. Data collection was conducted through tests and interviews, followed by analysis using the stages of data reduction, data presentation, and drawing conclusions. The research findings revealed that 6 students (17.65%) fell into the high category, 24 students (70.59%) into the moderate category, and 4 students (11.76%) into the low category. Students in the high category successfully met nearly all aspects of the ACER framework, with the exception of the generates a range of ideas aspect, where their performance was not yet optimal. Students in the moderate category demonstrated ability in the aspects of generates a number of ideas, adapts and manipulates ideas, and considers novelty. Meanwhile, students in the low category were only able to demonstrate ability in the aspect of generates a number of ideas. Overall, students’ mathematical creative thinking abilities fell into the moderate category.